Indirect Bonding Revisited - Hande Pamukçu; Ömür Polat Özsoy (Galenos Yayinevi, 2016)
In recent years, the popularity of indirect bonding increased due to advantages such as reduction of chair time and enhancement of patient comfort. Although the indirect bonding technique has improved over the years, the literature has shown different techniques of bracket placement; furthermore, new materials were specially developed for this technique. The aim of this article is to provide a review of the literature, advantages, disadvantages, and laboratory and clinical stages of the indirect bonding technique.